Vitamin E and lycopene reduce coal burning fluorosis-induced spermatogenic cell apoptosis via oxidative stress-mediated JNK and ERK signaling pathways. Issue 4 (31st July 2018) - Tian, Yuan; Xiao, Yuehai; Wang, Bolin; Sun, Chao; Tang, Kaifa; Sun, Fa
Abstract : Although fluoride has been widely used in toothpaste, mouthwash, and drinking water to prevent dental caries, the excessive intake of fluoride can cause fluorosis which is associated with dental, skeletal, and soft tissue fluorosis. Recent evidences have drawn the attention to its adverse effects on male reproductive system that include spermatogenesis defect, sperm count loss, and sperm maturation impairment. Fluoride induces oxidative stress through the activation of mitogen activated protein kinase (MAPK) cascade which can lead to cell apoptosis. Vitamin E (VE) and lycopene are two common antioxidants, being protective to reactive oxygen species (ROS)-induced toxic effects. However, whether and how these two antioxidants prevent fluoride-induced spermatogenic cell apoptosis are largely unknown. In the present study, a male rat model for coal burning fluorosis was established and the histological lesions and spermatogenic cell apoptosis in rat testes were observed. The decreased expression of clusterin, a heterodimeric glycoprotein reported to regulate spermatogenic cell apoptosis, was detected in fluoride-treated rat testes. Interestingly, the co-administration with VE or lycopene reduced fluorosis-mediated testicular toxicity and rescued clusterin expression. Further, fluoride caused the enhanced Jun N-terminal kinase (JNK, c-Jun) and extracellular signal-regulated protein kinase (ERK) phosphorylation, which was reduced by VE or lycopene. Thus, VE and lycopene prevent coal burning fluorosis-induced spermatogenic cell apoptosis through the suppression of oxidative stress-mediated JNK and ERK signaling pathway, which could be an alternative therapeutic strategy for the treatment of fluorosis.